6x-3=3-6x

Simple and best practice solution for 6x-3=3-6x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x-3=3-6x equation:


Simplifying
6x + -3 = 3 + -6x

Reorder the terms:
-3 + 6x = 3 + -6x

Solving
-3 + 6x = 3 + -6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6x' to each side of the equation.
-3 + 6x + 6x = 3 + -6x + 6x

Combine like terms: 6x + 6x = 12x
-3 + 12x = 3 + -6x + 6x

Combine like terms: -6x + 6x = 0
-3 + 12x = 3 + 0
-3 + 12x = 3

Add '3' to each side of the equation.
-3 + 3 + 12x = 3 + 3

Combine like terms: -3 + 3 = 0
0 + 12x = 3 + 3
12x = 3 + 3

Combine like terms: 3 + 3 = 6
12x = 6

Divide each side by '12'.
x = 0.5

Simplifying
x = 0.5

See similar equations:

| x/7-2=9/14 | | x-3=21.6 | | 4*2+1= | | 2x+16=y | | -18+x=10 | | 6+5y-1=8y+6-2y | | 2/-5*u=23 | | 550/1+4p=-9+2p | | 5a+7=4a-9 | | 2(y+2)-4=12 | | ((y-5)/(y-6))-1=((y-3)/(y-7)) | | 1/2b6=87 | | 4(4x-3)-6x=12-12-2x | | =p+p^2 | | 45y^2-60xy+20x^2=0 | | 3x-8=3x-5 | | 5/3x+1/3x=3x+40/3+5/3x | | 86+74=97+x | | x+22=38+55 | | 10*1000/3600 | | 21+x=40+4 | | -12=-2(3+3z) | | 10+15-?=21 | | u^2-3u=0 | | 10+15?=21 | | 3x+4=5+-10 | | 3(2-4x)/4-7=14 | | 8x-11=8x+8 | | -2(3x+4)=10 | | B-3=36 | | x+21=43+20 | | 2/5d=-10 |

Equations solver categories